A note on the polynomial surface fitting method for estimation of winds at different isobaric levels using the observed wind at 850 hPa level - BAVADEKAR , S. N.; KHALADKAR, R. M. (MAUSAM, 1992)
A third degree polynomial surface fitting technique is adopted to compute the winds at different isobaric levels for the limited area domain from 35°E to 140°E and 30° S to 40oN for the month of June. The polynomial surfaces are fitted to the ratios of the monthly mean winds at different isobaric levels with the 850 hPa winds. The surfaces are fitted to the II and v components of the winds separately. The winds for the level are then reconstructed using the computed coefficients and observed wind at 850 hPa. The results of the technique are presented and discussed in the paper.